Platelet‐rich plasma—Where do we stand today? A critical narrative review and analysis. Issue 1 (8th October 2020) - Arora, Gulhima; Arora, Sandeep
Abstract: "Sometimes you have to travel a long way to find what is near." This quote by Paulo Coelho stands true for platelet‐rich plasma (PRP) as we know of it today. Large strides have been made to understand this "youth" in blood, but there still seems a long way to go in our understanding of it. Despite advances, clarity in its preparation, biology, and the properties of the final product still remains elusive. The concepts of an ideal number or concentration of platelets in the final enriched plasma, best devices to prepare PRP, an ideal hardware, standard parameters for its preparation, the need for its activation or buffering of the final preparation or whether anticoagulants should be used or not, have evolved, since it was first described. The authors present an analysis of PRP present day status and its usefulness in field of medicine with a review of published literature from "Medline" (via "PubMed"), "Cochrane, " the Virtual Health Library, and Google Scholar related to PRP, its biology, types, and classifications, preparation, and use.